2012
DOI: 10.3319/tao.2012.05.22.01(wmh)
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impact Assessment for Sustainable Water Quality Management

Abstract: The goal of sustainable water quality management is to keep total pollutant discharges from exceeding the assimilation capacity of a water body. Climate change may influence streamflows, and further alter assimilation capacity and degrade river sustainability. The purposes of this study are to evaluate the effect of climate change on sustainable water quality management and design an early warning indicator to issue warnings on river sustainability. A systematic assessment procedure is proposed here, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…During flood events, water treatment facilities can become inundated, contaminating both overland and subsurface water (Coffey et al 2014;Boholm & Prutzer 2017;Parkinson et al 2021). Drought events particularly impact groundwater by concentrating contaminants and degrading the water quality (Tung et al 2012;Coffey et al 2014;Ekstrom et al 2017).…”
Section: Precipitationmentioning
confidence: 99%
“…During flood events, water treatment facilities can become inundated, contaminating both overland and subsurface water (Coffey et al 2014;Boholm & Prutzer 2017;Parkinson et al 2021). Drought events particularly impact groundwater by concentrating contaminants and degrading the water quality (Tung et al 2012;Coffey et al 2014;Ekstrom et al 2017).…”
Section: Precipitationmentioning
confidence: 99%
“…Many studies combined GCMs and hydrological models to assess water resource, streamflow, or ecosystem effects on catchment scales (Li et al 2009;Tung et al 2012;Chiang et al 2013;Niraula et al 2013). The GWLF, a physic-based model, was chosen as the hydrological model for assessing streamflow impacts in this study.…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Climate change has different impacts on river discharge worldwide (Thodsen 2007;Sato et al 2012;Hong et al 2014). Previous studies that used scenarios from the Third Assessment Report (TAR) of the Intergovernmental Panel on Climate Change (IPCC) indicated that streamflow in Taiwan will decline during the dry season and increase during the wet season (Tung 2001;Yu et al 2002;Li et al 2009;Tung et al 2012). Taiwan's water demand has grown under global climate change and rapid social and economic development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation